MOTIVASI PETERNAK PLASMA AYAM BROILER DALAM BERMITRA DI KECAMATAN KAMPAR KIRI TENGAH KABUPATEN KAMPAR (STUDI KASUS PT. MITRA ANUGERAH SATWA) - Prasetyo, Mohd Andi; Sayamar, Eri; ', Cepriadi (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
This research aims to (1) analyse the partnership system held by PT. Mitra Anugerah Satwa; (2) analyse the variables who motivate broiler breeder in partnership; (3) describe the problems that occur in a partnership between farmers with firm partner. This research used descriptive with quantitative and qualitative data, data collection held by interview with questionnaire. Data analysis was done descriptively with Likert's Summated Rating Scale (LSRS) and factor analysis. The result showed that partnersip system was core-plasma, where firm as core and breedes as plasma. The firm helped the plasma in terms of capital by providing production means. But, the plasma becomes weaker position because the agreement given by firm to be accepted breeders without prior negotiation. The result of factor analysis showed that 7 (seven) variables qualified to produce 1 (one) motivation formation. The main motivation that influenced breeders in partnership with PT. Mitra Anugerah Satwa in Kampar Kiri Tengah District Kampar Regency were awards, working conditions, employment, compensation, company policies, achievements, and monitoring. The problems that occur in a partnership between farmers with firm partner (a) problems in pre-production phase were the agreement made by firm without negotiated with breeders (100%), the contract of production mean’s price determined unilaterally (100%), and the deposit or guarantee militated breeders (60%); (b) problem in production phase was lack of clarity in the quality standards of production means by firm (100%); (c) problem in post-production phase no dominant issue; and (d) problems in supporting phase were the absence of arbitration (100%) and the lack of supporting institutions (100%).     Keywords : Broiler, Motivation of Breeder, Partnership